Barriers and facilitators to seeking care for persons with acute brain infections: a cross sectional study - Nair, Vasundharaa S.; Thomas, Priya Treesa; Sekar, Kasi; Netravathi , M. (International Journal Of Community Medicine And Public Health, 2023)
Background: Acute brain infections including encephalitis are less common but serious conditions characterized by the inflammation of the brain requiring immediate accurate diagnosis and management. For many infections appropriate therapies exist, but the outcome is often less desirable because of failure to receive appropriate treatment on time due to multiple factors. The aim of the study was to understand the barriers and facilitators towards receiving care for persons with acute brain infections in a low resource setting. Methods: The study design was cross sectional exploratory study. Consecutive patients presenting to neurology department of a tertiary referral care center for Neuropsychiatry in South India from July 2020 to September 2020 with the diagnosis of acute brain infections were assessed using the modified Kuppuswamy scale, Glasgow coma scale, the pathway scale: encounter form, patient centered health services in India and client socio-demographic and service receipt inventory. Results: A total of 110 participants, both male and female, were recruited for the study. The average age was 39.64±16.5 years, with more female (65.45%) representation. 29% of individuals reported continued use of traditional practices while seeking care for the brain infections. Costs associated with care increased with the increase in duration of infection. There are major barriers and facilitators which either prohibit or facilitate care for persons with acute brain infections. Conclusions: Acute brain infections continuing to be a public health challenge in developing country context, and the recognition that the delay in treatment causes significant disability, it becomes imperative to focus on the social, cultural, economic, environmental factors to understand the barriers and facilitators to health seeking among this population.